Adaptive Multi-Scale Fusion for Infrared and Visible Object Detection in YOLOv8 - Ren, Zheng (Journal of Theory and Practice of Engineering Science, 2024)
Object detection in infrared images presents unique challenges due to varying environmental conditions and the inherent characteristics of thermal data. This paper introduces a novel Multi-scale Feature Fusion and Adaptive Modality Weighting (MFAW) module integrated into the YOLOv8 architecture to enhance object detection performance in infrared imagery. By leveraging the strengths of both infrared and visible light data, the proposed method effectively addresses issues related to feature extraction and fusion. Comprehensive experiments conducted on the LLVIP and VEDAI datasets demonstrate that our approach significantly outperforms existing models in terms of mean Average Precision (mAP), achieving superior accuracy across multiple detection scenarios. The results indicate the effectiveness of the MFAW module in improving the adaptability and robustness of object detection systems, particularly in low-light conditions.